Acceptance and adoption of biofortified crops in low- and middle-income countries: a systematic review - Talsma, Elise F.; Melse-Boonstra, Alida; Brouwer, Inge D. (Oxford University Press, 2017)
Context: Biofortification of staple crops is a promising strategy for increasing the nutrient density of diets in order to improve human health. The willingness of consumers and producers to accept new crop varieties will determine whether biofortification can be successfully implemented. Objective: This review assessed sensory acceptance and adoption of biofortified crops and the determining factors for acceptance and adoption among consumers and producers in low- and middle-income countries. Data sources: PubMed, Scopus, and Web of Science were searched for published reports. Unpublished studies were identified using an internet search. Study selection: From a total of 1669 records found, 72 primary human research studies published in English or Spanish met the criteria for inclusion. Data extraction: Data were extracted from each identified study using a standardized form. Results: Sensory acceptability (n = 40) was the most common topic of the studies, followed by determinants of acceptance (n = 25) and adoption (n = 21). Of crops included in the studies, sweet potato and maize were the most studied, whereas rice and pearl-millet were the least investigated. Overall, sensory acceptance was good, and availability and information on health benefits of the crops were the most important determinants of acceptance and adoption. Conclusions: Changes to the sensory qualities of a crop, including changes in color, did not act as an obstacle to acceptance of biofortified crops. Future studies should look at acceptance of biofortified crops after they have been disseminated and introduced on a wide-scale.